MUSIC STRUCTURE ANALYSIS OF THE SONG SUNO LOWALANGI ARRANGEMENT BY BRIAN HAREFA - Galingging, Kamaluddin; Waruwu, Happy Majesty; Saragih, Ronald H; Simangunsong, Emmi; Situmorang, Yulia Ruth (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
This research aims to discuss the structure of the musical arrangement of the song "Suno Lowalangi" by Brian Harefa. Suno Lowalangi means Praise the Lord, which is one of the songs in the ZinunÖ Book (songs of praise), BNKP No. 69, and is used in BNKP congregational worship using a single organ accompaniment, tempo 99-104 (moderato). Suno Lowalangi, meaning "praise God," is a song whose melody is adopted from the song "From the Islands and Continents" with translation into the Nias language (li niha). In 2013, Brian Harefa, an artist from Nias, composed the song "Suno Lowalangi" into a jazz music concept accompanied by piano, bass guitar, and drums. The musical arrangement of the song "Suno Lowalangi" by Brian Harefa makes the song a contemporary musical work that comes from the musical concept as in the Zinuno Book. This research was carried out using descriptive-analytical qualitative research methods through a transcription analysis study approach, namely an activity of changing sound (audio) signals into notational form, which is then analyzed using theories of musical structure analysis. The song "Suno Lowalangi" is one of the song titles in the Zinunö Book (hymns) used in congregational worship at the Banua Niha Keriso Protestant (BNKP) church. This song is recorded in the Zinunő Book No. 069, which is included in the theme fa'atumbu yesu (the birth of Jesus Christ), so this song is generally sung in almost every Christmas celebration service. "Suno Lowalangi," which means "praise the Lord," is a translation of the song "From the Island and the Continent," which is also a Christmas-themed song. Suno Lowalangi adopts some of the lyrics and melody that are exactly the same as the song "From the Island and the Continent," only the lyrics are translated into the Nias language (li niha). The process of translating the lyrics into the Nias language was carried out so that it could be easily accepted by the Nias people as the majority of the BNKP church congregation members. The song Suno Lowalangi has been adopted into the Zinunö Book since 2014. The song "Suno Lowalangi" has a diatonic scale and is sung with a tempo of 94-104 (moderato) with a single organ accompaniment. In 2013, Brian Harefa gave a new color to the musicality of the song "Suno Lowalangi" in a form that was slightly different from the presentation of the song at the BNKP congregation's worship. The use of improvisation and syncopation in the chords and melody made the song "Suno Lowalangi" come out of its musical concept as a hymn in church worship, becoming a jazz genre song with a more modern musical concept. Some of the instruments used to accompany the song are piano, bass, and drums.